John Dewey and contemporary challenges to democratic education - Festl, Michael G. (New York, NY : Routledge, 2025)
"This volume reconsiders pragmatist conceptions of democratic education, especially John Dewey's. It addresses what democratic education can mean in the face of the current threats that are undermining democracy. Since the middle of the twentieth century, liberal philosophers have been skeptical of fostering values through public education. Since liberal democracy must embrace different worldviews, education, especially public education, must refrain from teaching values as far as possible. Given the recent undermining of democratic nation states and their liberal foundations, this educational abstinence can be interpreted as one of the drivers of the current crisis of democracy. This volume sketches how a renewed democratic education, in the model of John Dewey and other forms of pragmatist educational philosophy, might look today. The volume identifies the conceptual, political, and technological challenges to education and democracy, and explores how a new democratic education could translate into the classroom. John Dewey and Contemporary Challenges to Democratic Education will appeal to scholars and advanced students interested in pragmatism and American philosophy, philosophy of education, and political philosophy"--
Introduction / Michael G. Festl -- John Dewey's method of intelligence is often threatening, but is it objectionable? : why schools need to address fear of change if we hope to renew democracy in our time / Jeff Frank -- John Dewey, Jane Addams, and the pragmatist road to democracy / Maura Striano -- Education, text, and context : between John Dewey and Stanley Cavell / Filippo Sanna -- Populism, democratic education and a look at the Ukrainian war /Jürgen Oelkers -- Worldview, democracy, and education : lessons from Poland : practice and theory, the past and the future / Agnieszka Hensoldt -- Deweyan democracy and education in a 'society of broadcasters' / Julian Culp -- Democracy without autonomy? : information technology's manipulation of experience and morality / David L. Hildebrand -- Philosophy for children as a via media between democratic and anarchist education / Maria Miraglia -- The economy and democracy as a way of living : how to create democratic attitudes within economic ethics / Bettina Hollstein -- Art education and democracy : John Dewey and contemporary art education practice / Leonard J. Waks.
Keywords: Dewey, John, -- 1859-1952.; Democracy and education; Public schools; Education -- Philosophy; Education -- Aims and objectives; PHILOSOPHY / Movements / Pragmatism; PHILOSOPHY / Political; EDUCATION / Philosophy & Social Aspects